Listening to stakeholders in the prevention of gender-based violence among young people in Spain: a qualitative study from the positivMasc project - Jorge Marcos-Marcos; Krizia Nardini; Erica Briones-Vozmediano; Carmen Vives-Cases (BMC, 2023)
Abstract Objective This study seeks to deepen current knowledge of the phenomenon of gender-based violence (GVB) among young people in Spain, identifying the main challenges in terms of prevention from the perspective of key stakeholders in the field. Methods 23 semi-structured qualitative interviews were performed with professionals whose work involves youth and comes from different areas: social work, policy making, youth education, feminist and LGBTQ activism and anti-violence masculinities engagement (13 women and 10 men). Results Among the main challenges identified by stakeholders in relation to GBV preventive strategies in young populations there is a need to focus on transformative programmes within educational settings. The findings indicate that specific programs and interventions in this area may not be yielding the expected effectiveness. This outcome could be attributed less to a lack of resources and more to a failure to address the core issues and challenges adequately. Thus, the results underline that intervention programmes should emphasise equitable gender norms and gender relations and incorporate content on anti-violence masculinities. Finally, a pivotal aspect seen by professionals to facilitate GBV prevention is the design and development of interventions based on participatory and active approaches, close to young people's everyday situations. The results also draw attention to the need to analyse the impact of new forms of violence in greater depth, especially those that occur through information and communication technologies. Conclusion Among other implications for policy and practice, the study points to the need to articulate interventions designed to work simultaneously at different levels of influence acting on people.